(untitled) (Philological Studies, 2019)
In his essay Reflections on Exile, Edward Said points that, while “most people are principally aware of one culture, one setting, one home; exiles are aware of at least two, and this plurality of vision gives rise to an awareness of simultaneous dimensions, an awareness that – to borrow a phrase from music – in contrapuntal”. This text examines this contrapuntal awareness of the characters from the novels The Museum of Unconditional Surrender and Ministry of Pain by Dubravka Ugrešić.